1977
DOI: 10.1177/00220345770560091401
|View full text |Cite
|
Sign up to set email alerts
|

Levan Production by a Strain of Rothia: Activation of Complement Resulting in Cytotoxicity for Human Gingival Cells

Abstract: An extracellular polysaccharide identified as a levan has been isolated from Rothia dentocariosa, strain 477 serotype 2. The levan produced by strain 477 has been found to activate the complement cascade in the absence of specific antibodies. This activation was found to be cytotoxic for human gingival cells in tissue culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated sucrosedependent production of extracellular levan by oral microorganisms such as Streptococcus salivarius (12,33,39), Actinomyces viscosus (17,25,32,34,42), Streptococcus mutans (3,4,7,47), and Rothia dentocariosa (27). The presence of levan in dental plaque also has been confirmed (5,29,46), and several studies have demonstrated or inferred that at least part of this levan can be degraded by plaque microbial enzymes (6,14,16,30).…”
mentioning
confidence: 96%
“…Several studies have demonstrated sucrosedependent production of extracellular levan by oral microorganisms such as Streptococcus salivarius (12,33,39), Actinomyces viscosus (17,25,32,34,42), Streptococcus mutans (3,4,7,47), and Rothia dentocariosa (27). The presence of levan in dental plaque also has been confirmed (5,29,46), and several studies have demonstrated or inferred that at least part of this levan can be degraded by plaque microbial enzymes (6,14,16,30).…”
mentioning
confidence: 96%
“…The presence of serum antibody against Actinomyces species in human periodontal lesions has also been demonstrated (36). Moreover, levan produced by Actinomyces species as well as several other oral microorganisms has been shown to be a mitogen for human B lymphocytes (11) and to be an activator for alternative complement pathway (4,17). It is thought that levan present in periodontal lesions interacts with the immune system and plays an important role in the induction and progress of periodontal disease.…”
Section: Discussionmentioning
confidence: 98%
“…Levan may be a structural polysaccharide in plaque (5,8,9) and may be utilized by plaque flora as a source of carbohydrate, a process which is related to acid production (24,33). Furthermore, levan has been shown to be mitogenic for human B lymphocytes (11) and to activate the alternative complement pathway (4,17,23). These properties could be important in the pathogenicity of periodontal disease.…”
mentioning
confidence: 99%
“…The presence of fructan in dental plaque has been demonstrated by several authors (19,23,24). Fructan in dental plaque is synthesized extracellularly by many oral bacteria such as Streptococcus salivarius (11,12,14,16,27,31), Streptococcus mutans (3,4,5,8,11), Actinomyces viscosus (19,20,25,26,28,29,36,39), and Rothia dentocariosa (21). However, the fructan produced in dental plaque is not homogeneous.…”
Section: P-(26)-fructofuranosidasementioning
confidence: 99%